ANALISIS ARUS DAN SEBARAN SEDIMEN TERSUSPENSI DAMPAK TAMBANG TIMAH DI LAUT (KASUS PERAIRAN PULAU RANGSANG KABUPATEN KEPULAUAN MERANTI) - Mubarak Mubarak; Edison Edison; Sri Fitria R (Jurnal Ilmu Lingkungan, 2014)
Utilization of marine natural resources at this current becoming one of the option thatis used by several Indonesian regions as motors of regional development. One of thenatural resources potential is tin mining. Tin mining over the ocean not only provideseconomic value, but also resulting negative impacts on marine waters. The alleged ofnegative impact is the increasing of suspended sediment in the waters due to leaching ofmining activities on the ship. Current circulation patterns that generated by tidal ofPulau Rangsang waters Regency of Meranti Islands, when the tide to ebb is heading tothe Southward and when the ebb to tide is heading to northward. The resultant ofcurrents circulation tend to align with the mainland of Pulau Topang. Suspendedsediment transport generated by ocean currents, showing the distribution of thesuspended sediment concentration of 0.08 kg/m3 or 80 ppm spreads about 2 km fromthe material source.